Research on Power Load Modeling Based on Improved Perturbed Method - Guoping Shi; Jun Liang; Xiangsheng Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper introduces a conventional synthesis power load model considering distribution network in PSASP, through analyzing the model structure and achieving process, proposes a power load model parameter identification method based on improved perturbed method. The paper gives parameters identification method of complete synthesis load model, including reactive power compensator parameters. The parameters identification method combines parameter identification process with sensitivity analyzing process together, not only can get model parameters but also can obtain the sensitivity of all parameters, which saves computing time and reduces the amount of calculation, the final simulation results prove the method is effective and feasible. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5113